Parental Parenting Patterns and Social Media Use: Students’ Social Attitudes Building - Puji Anita Eka Prativiningsih; Muhammad Hanif; Parji Parji (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The rapid expansion of digital technology has fundamentally reshaped adolescents’ social interactions, raising concerns regarding the formation of social attitudes within educational settings. This study aims to examine the interplay between parenting styles and the intensity of social media use in shaping students’ social attitudes at the junior secondary school level. Methodology: Employing a qualitative case study approach, data were collected through in-depth interviews with students and parents, systematic classroom observations, and documentation analysis, and were validated using data triangulation techniques. Main Findings: The findings reveal that authoritative (democratic) parenting, characterized by a balanced combination of behavioral demands and emotional responsiveness, plays a crucial role in fostering positive social attitudes, including self-regulation, empathy, and collaborative skills. Students raised within a democratic family climate demonstrate internalized moral reasoning, enabling them to maintain socially appropriate behavior without reliance on external supervision. In contrast, excessive social media use is associated with social withdrawal, fragmented attention, and diminished quality of face-to-face interactions in school contexts. High levels of digital engagement were found to displace opportunities for direct interpersonal communication, leading to what can be described as social atrophy and alienation. Novelty/Originality of this study: This study contributes to the literature by highlighting the protective function of authoritative parenting in mitigating the negative social effects of intensive digital media use. The results underscore that the family remains a critical socialization arena in the digital era, capable of strengthening adolescents’ social resilience when supported by effective communication and guided autonomy.